Mechanistic Aspects of Gas‐Phase Hydrogen‐Atom Transfer from Methane to [CO].+ and [SiO].+: Why Do They Differ?. Issue 21 (27th March 2013) - Dietl, Nicolas; Troiani, Anna; Schlangen, Maria; Ursini, Ornella; Angelini, Giancarlo; Apeloig, Yitzhak; de Petris, Giulia; Schwarz, Helmut
Abstract The reactivity of the two diatomic congeneric systems [CO].+ and [SiO].+ towards methane has been investigated by means of mass spectrometry and quantum‐chemical calculations. While [CO].+ gives rise to three different reaction channels, [SiO].+ reacts only by hydrogen‐atom transfer (HAT) from methane under thermal conditions. A theoretical analysis of the respective HAT processes reveals two distinctly different mechanistic pathways for [CO].+ and [SiO].+, and a comparison to the higher metal oxides of Group 14 emphasizes the particular role of carbon as a second‐row p element.